The Effectiveness of Strategy-based Reading Instruction (SBRI) and Reciprocal Teaching (RT) For Teaching Reading Comprehension in EFL Context - Semi Sukarni (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
The objective of the study is to investigate the effectiveness of Strategy-based Reading Instruction (SBRI) and Reciprocal Teaching (RT) for teaching readingcomprehension. The research had been done in English Education Program of Purworejo Muhammadiyah University involving two classes of the fifth semester students. It is an experimental study that had been done by pretest-treatment-posttest. The reading comprehension test adopted from TOEFL and FCE was used to collect the data of student reading proficiency.The data were analyzed by using descriptive and inferential anlysis. The finding shows that SBRI is more effective in improvingStudents Reading Proficiency as this has been proved by different mean score between SBRI class and RT class. The mean score of SBRI class is 66.4which lays in the Good level, while the mean of RT class in only 61.4 which lays in the Sufficient level. The inferential analysis shows that the t-test is 2.27 with the significant level 0.027 (<0.05). It means that Ho is rejected and Ha is accepted.